PENGARUH KONSELING TENTANG KB SUNTIK 3 BULAN TERHADAP PENGETAHUAN IBU DI WILAYAH KERJA PUSKESMAS BUTUH KABUPATEN PURWOREJO - Nindya Kurniawati; Lutfi Nur Azizah (Jurnal Komunikasi Kesehatan, 2022)
Information is very important for someone, lack of information can result in a person's lack of knowledge. Based on a preliminary study of 10 family planning acceptors who answered questions about the advantages, disadvantages, indications, contraindications, and side effects of 3-month injections, there were 6 people who could not answer questions and 4 people who could answer questions. The purpose of the study was to determine the effect of counseling on 3-month injection family planning on mother's knowledge in the Work Area of the Puskesmas Need Purworejo. The research method used a pre-experimental design with a one-group pretest-posttest approach. The total population of all mothers who use injection contraception for 3 months and the number of samples is 35 people, with the sampling technique Accidental Sampling. The research instrument used a questionnaire. Data analysis used paired t-test. The results of the Shapiro-Wilk normality test p value> (0.05), the paired t-test test significance value (p) 0.00 < (α) 0.05 and the lower and upper values do not pass zero (0), the average value before counseling 17.43 and before counseling 22.03. There is an effect of counseling about 3-month injection KB on mother's knowledge with a difference of 4.6 pretest and posttest scores.